Peritoneal Inclusion Cyst in a pre-pubertal male - Mehran Hiradfar; Reza Shojaeian; Nona Zabolinejad; Reza Nazarzadeh; Ali Azadmand (Iranian Journal of Pediatric Surgery, 2016)
Introduction Peritoneal inclusion cyst (PIC) is a cyst lined with mesothelium and usually full of fluids in the pelvis and it is most usually seen in young women and rarely, they may occur in males.